Non-aqueous electrolyte secondary battery

By setting flat and bent portions of different densities in the negative electrode mixed material layer of the nonaqueous electrolyte secondary battery, the problem of electrolyte being extruded due to expansion of the electrode body is solved, and the circulation characteristics and capacity maintenance rate of the battery are improved. Prevent lithium precipitation.

CN110970653BActive Publication Date: 2024-12-13SANYO ELECTRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201910762656.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-28
Filing Date
2019-08-16
Publication Date
2024-12-13
Estimated Expiration
2040-02-20

AI Technical Summary

Technical Problem

In a flat-shaped winding non-aqueous electrolyte secondary battery having a flat portion and a curved portion, the electrode body expands during charging and discharging, causing the electrolyte to be extruded, resulting in insufficient electrolyte and reduced circulation characteristics.

Method used

By providing a flat portion and a bent portion with different filling densities in the negative electrode mixed material layer, the filling density of the bent portion is ensured to be higher than that of the flat portion, and the electrolyte is stored and returned to the electrolyte by using the bent portion to prevent insufficient electrolyte.

Benefits of technology

The cycle characteristics and capacity maintenance rate of the battery are improved, and the precipitation of lithium on the negative electrode surface is prevented and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110970653B_ABST
    Figure CN110970653B_ABST
Patent Text Reader

Abstract

In a non-aqueous electrolyte secondary battery having a flat wound electrode body with a flat portion and a curved portion, the cycle characteristics are improved. In a non-aqueous electrolyte secondary battery as an example of an embodiment, the negative electrode mixed material layer includes a first region located at the flat portion of the electrode body and a second region located at a pair of curved portions, and the ratio B / A of the packing density B of the second region to the packing density A of the first region is greater than 0.75 and less than 0.95. Furthermore, in a cross section perpendicular to the axial direction passing through the axial center of the electrode body, the ratio SB / SA of the cross-sectional area SB of the pair of curved portions to the cross-sectional area SA of the flat portion is greater than 0.28 and less than 0.32.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nonaqueous electrolyte secondary battery. Background Art

[0002] In the past, a non-aqueous electrolyte secondary battery having a flat winding electrode body is known, wherein the electrode body is formed by winding a positive electrode and a negative electrode with a separator, and has a flat portion and a pair of curved portions. Patent document 1 discloses a non-aqueous electrolyte secondary battery having a negative electrode, in which the packing density of the negative electrode mixed material layer at the curved portion is smaller than that of the flat portion of the electrode body for the purpose of suppressing deformation of the electrode plate accompanying the charging and discharging of the battery. In addition, Patent document 1 states that the difference in packing density between the flat portion and the curved portion is preferably set to within 5%.

[0003] Prior Art Literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2006-278182 Summary of the invention

[0006] Problems to be solved by the invention

[0007] However, in a non-aqueous electrolyte secondary battery having a flat wound electrode body with a flat portion and a curved portion, there is a problem that if the electrode body expands with charge and discharge, the non-aqueous electrolyte immersed in the electrode body is squeezed out to the outside of the electrode body, so that the liquid amount is greatly reduced and the cycle characteristics are reduced. In particular, since the volume of the flat portion changes greatly with charge and discharge, there are the following situations: the amount of electrolyte is easily reduced in the flat portion, the electrolyte required for the battery reaction is insufficient, or the electrolyte dries up, so-called liquid drying up. There is still room for improvement in the previous technology, including the technology disclosed in Patent Document 1, to suppress the reduction in cycle characteristics caused by the reduction in the amount of electrolyte immersed in the flat portion of the electrode body.

[0008] Technical solutions to solve problems

[0009] A nonaqueous electrolyte secondary battery as one embodiment of the present invention comprises: a wound electrode body formed into a flat shape, the electrode body being formed by winding a positive electrode including a positive electrode mixed material layer and a negative electrode including a negative electrode mixed material layer through a separator, and having a flat portion and a pair of curved portions; a nonaqueous electrolyte; and a battery case accommodating the electrode body and the nonaqueous electrolyte. The negative electrode mixed material layer comprises a first region located in the flat portion of the electrode body and a second region located in the pair of curved portions, the ratio (B / A) of the packing density (B) of the second region to the packing density (A) of the first region is 0.75 or more and 0.95 or less, and in a cross section perpendicular to the axial direction passing through the axial center of the electrode body, the ratio (SB / SA) of the cross-sectional area (SB) of the pair of curved portions to the cross-sectional area (SA) of the flat portion is 0.28 or more and 0.32 or less.

[0010] Effects of the Invention

[0011] According to one embodiment of the present invention, in a non-aqueous electrolyte secondary battery having a flat wound electrode body with a flat portion and a curved portion, the cycle characteristics can be improved. The non-aqueous electrolyte secondary battery of the present invention has a high capacity retention rate and output after a cycle test, and lithium precipitation on the negative electrode surface is unlikely to occur. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a front view of a nonaqueous electrolyte secondary battery as an example of an embodiment, and shows a state where a battery case and a front surface portion of an insulating sheet are removed.

[0013] Figure 2 It is a top view of a nonaqueous electrolyte secondary battery as an example of the embodiment.

[0014] Figure 3 It is a cross-sectional view of an electrode body as an example of an embodiment.

[0015] Description of Reference Numerals

[0016] 1 Square outer body

[0017] 2 Sealing plate

[0018] 3 Electrode body

[0019] 4 Positive electrode

[0020] 4a, 5a Core exposed part

[0021] 5 Negative electrode

[0022] 6. Positive electrode collector

[0023] 7 Positive terminal

[0024] 7a, 9a Flange

[0025] 8 Negative electrode collector

[0026] 9 Negative terminal

[0027] 10, 12 Internal insulation components

[0028] 11, 13 External insulation components

[0029] 14 Insulation sheet

[0030] 15 Gas exhaust valve

[0031] 16 Electrolyte injection hole

[0032] 17 sealing plug

[0033] 20 Flat part

[0034] 21 Bending part

[0035] 30 Partition

[0036] 40 positive electrode core

[0037] 41. Positive electrode mixed material layer

[0038] 50 Negative electrode core

[0039] 51 Negative electrode mixed material layer

[0040] 51A Area 1

[0041] 51B Second Area

[0042] 100 Non-aqueous electrolyte secondary battery

[0043] 200 Battery housing DETAILED DESCRIPTION

[0044] According to one embodiment of the present invention, as described above, in a non-aqueous electrolyte secondary battery having a flat wound electrode body having a flat portion and a curved portion, the cycle characteristics can be improved. In the non-aqueous electrolyte secondary battery involved in the present invention, when the electrode body expands due to the expansion of the negative electrode during charging, the non-aqueous electrolyte squeezed out from the flat portion of the electrode body is effectively stored in the curved portion of the electrode body. Moreover, when the volume of the flat portion shrinks, the non-aqueous electrolyte stored in the curved portion returns to the flat portion, thereby suppressing the shortage of electrolyte in the flat portion. Therefore, it can be considered that according to the non-aqueous electrolyte secondary battery involved in the present invention, the reduction in cycle characteristics caused by the reduction in the amount of electrolyte immersed in the flat portion of the electrode body can be suppressed.

[0045] Hereinafter, an example of an embodiment of the present invention will be described in detail. In this embodiment, although a square battery having a battery case 200 as a square metal case is exemplified, the battery case is not limited to a square shape, and for example, a battery case composed of a laminate sheet including a metal layer and a resin layer may be used. In addition, in this specification, if the description of "approximately to" is described as an example of approximately the same, it means both a completely identical state and a state that is considered to be substantially the same.

[0046] like Figure 1 as well as Figure 2 As shown, the non-aqueous electrolyte secondary battery 100 comprises: a flat wound electrode body 3 formed by winding the positive electrode and the negative electrode with a separator, and having a flat portion and a pair of curved portions; a non-aqueous electrolyte; and a battery case 200 for containing the electrode body 3 and the non-aqueous electrolyte. The battery case 200 includes a square outer body 1 with a bottom and a cylindrical shape having an opening and a sealing plate 2 for sealing the opening of the square outer body 1. The square outer body 1 and the sealing plate 2 are both made of metal, preferably aluminum or an aluminum alloy.

[0047] The square outer casing 1 has a bottom that is roughly rectangular when observed from the bottom surface and a side wall portion that is vertically arranged around the bottom. The side wall portion is formed perpendicular to the bottom. The size of the square outer casing 1 is not particularly limited. As an example, the horizontal length is greater than 130 mm and less than 160 mm, the height is greater than 60 mm and less than 70 mm, and the thickness is greater than 15 mm and less than 18 mm. In this specification, for ease of explanation, the direction along the length direction of the bottom of the square outer casing 1 is referred to as the "lateral direction" of the outer casing, the direction perpendicular to the bottom extending from the side wall portion is referred to as the "height direction", and the direction perpendicular to the lateral and height directions is referred to as the "thickness direction".

[0048] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For the non-aqueous solvent, for example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof can be used. The non-aqueous solvent may contain a halogen substitution body obtained by replacing at least a portion of the hydrogen of these solvents with a halogen atom such as fluorine. For the electrolyte salt, for example, a lithium salt such as LiPF6 is used. The battery housing 200 (square outer body 1) can accommodate a non-aqueous electrolyte in an amount of more than 55g and less than 75g. In particular, when the square outer body 1 has the above-mentioned size, the amount of the non-aqueous electrolyte is preferably more than 55g and less than 75g.

[0049] The positive electrode is an elongated body having a positive electrode core body made of metal and positive electrode mixed material layers formed on both sides of the core body, and a strip-shaped core body exposure portion 4a is formed at one end in the short side direction, where the positive electrode core body is exposed along the length direction. Similarly, the negative electrode is an elongated body having a negative electrode core body made of metal and negative electrode mixed material layers formed on both sides of the core body, and a strip-shaped core body exposure portion 5a is formed at one end in the short side direction, where the negative electrode core body is exposed along the length direction. The electrode body 3 has the following structure, that is, the positive electrode and the negative electrode are wound with a separator in a state where the core body exposure portion 4a of the positive electrode is arranged at one end side in the axial direction and the core body exposure portion 5a of the negative electrode is arranged at the other end side in the axial direction.

[0050] The positive electrode collector 6 is connected to the laminated portion of the exposed core portion 4a of the positive electrode, and the negative electrode collector 8 is connected to the laminated portion of the exposed core portion 5a of the negative electrode. The preferred positive electrode collector 6 is made of aluminum or an aluminum alloy. The preferred negative electrode collector 8 is made of copper or a copper alloy. The positive terminal 7 has a flange portion 7a arranged on the battery exterior side of the sealing plate 2 and an insertion portion inserted into the through hole provided in the sealing plate 2, and is electrically connected to the positive electrode collector 6. In addition, the negative terminal 9 has a flange portion 9a arranged on the battery exterior side of the sealing plate 2 and an insertion portion inserted into the through hole provided in the sealing plate 2, and is electrically connected to the negative electrode collector 8.

[0051] The positive electrode collector 6 and the positive electrode terminal 7 are fixed to the sealing plate 2 via the inner insulating member 10 and the outer insulating member 11, respectively. The inner insulating member 10 is arranged between the sealing plate 2 and the positive electrode collector 6, and the outer insulating member 11 is arranged between the sealing plate 2 and the positive electrode terminal 7. Similarly, the negative electrode collector 8 and the negative electrode terminal 9 are fixed to the sealing plate 2 via the inner insulating member 12 and the outer insulating member 13, respectively. The inner insulating member 12 is arranged between the sealing plate 2 and the negative electrode collector 8, and the outer insulating member 13 is arranged between the sealing plate 2 and the negative electrode terminal 9.

[0052] The electrode body 3 is contained in the square outer body 1 in a state covered by the insulating sheet 14. The sealing plate 2 is connected to the opening edge of the square outer body 1 by laser welding or the like. The sealing plate 2 has an electrolyte injection hole 16, and after the non-aqueous electrolyte is injected into the battery case 200, the electrolyte injection hole 16 is sealed with a sealing plug 17. On the sealing plate 2, a gas discharge valve 15 for discharging gas when the pressure inside the battery becomes above a given value is formed.

[0053] Below, refer to Figure 3 The electrode body 3 , in particular, the negative electrode 5 and the separator 30 constituting the electrode body 3 will be described in detail. Figure 3 A cross section perpendicular to the axial direction and passing through the axial center of the electrode body 3 (hereinafter, sometimes referred to as “cross section X”) is shown.

[0054] like Figure 3 As shown, the electrode body 3 is a wound electrode body 30 formed into a flat shape by winding the positive electrode 4 and the negative electrode 5 with a separator therebetween and having a flat portion 20 and a pair of curved portions 21. In this specification, for the sake of convenience, the direction in which the flat portion 20 and the pair of curved portions 21 are arranged is referred to as the "width direction" of the electrode body 3, and the direction perpendicular to the axial direction and the width direction is referred to as the "thickness direction". In this embodiment, the electrode body 3 is accommodated in the square outer body 1 in a state where the axial direction of the electrode body 3 is along the lateral direction of the square outer body 1 and the width direction of the electrode body 3 is along the height direction of the square outer body 1.

[0055] The flat portion 20 is a portion of the electrode (positive electrode 4 and negative electrode 5) that is arranged approximately parallel to each other in the width direction without being bent. A pair of curved portions 21 is a portion of the electrode that is bent into an arc shape, and in the curved portion 21, the electrode is bent to bulge outward in the width direction. A pair of curved portions 21 are formed on both sides of the electrode body 3 in the width direction so as to clamp the flat portion 20. When observed in cross section (cross section X), the flat portion 20 has a generally rectangular shape, and each curved portion 21 has a generally semicircular shape. The radii of each curved portion 21 are, for example, equal to each other, and twice the value of the radius is equal to the thickness (d) of the flat portion 20 (that is, the radius of the curved portion 21 is d / 2).

[0056] In the electrode body 3, as described above, the core exposed portion 4a of the positive electrode 4 is arranged on one end side in the axial direction, and the core exposed portion 5a of the negative electrode 5 is arranged on the other end side in the axial direction. In addition, the entire area of ​​the positive electrode mixed material layer 41 is opposed to the negative electrode mixed material layer 51 via the separator 30. As will be described in detail later, the electrode body 3 is manufactured by compressing the wound body formed by winding the positive electrode 4 and the negative electrode 5 into a cylindrical shape via the separator 30 at a given pressure in the radial direction and forming it into a flat shape.

[0057] The electrode body 3 includes, for example, two long separators 30 configured to sandwich the positive electrode 4, and is arranged in the order of separator 30 / positive electrode 4 / separator 30 / negative electrode 5 from the inner side of the winding of the electrode body 3. In this case, the length of each separator 30 is preferably at least longer than the length of the positive electrode 4. In addition, the width of the separator 30 is shorter than the axial length (L) of the electrode body 3, and at least longer than the width of the positive electrode mixed material layer 41 (the length K of the positive electrode mixed material layer 41 along the axial direction of the electrode body 3). The width of the separator 30 may be longer than the width of the negative electrode mixed material layer 51.

[0058] For the electrode body 3, in the cross section X, the ratio (SB / SA) of the cross-sectional area (SB) of the pair of curved portions 21 to the cross-sectional area (SA) of the flat portion 20 is 0.28 or more and 0.32 or less. When the cross-sectional area ratio (SB / SA) is less than 0.28, the storage function of the non-aqueous electrolyte of the curved portion 21 is not fully reflected, and the cycle characteristics of the battery are reduced. On the other hand, when the cross-sectional area ratio (SB / SA) exceeds 0.32, the output characteristics of the battery are reduced. The cross-sectional area ratio (SB / SA) is particularly preferably 0.29 or more and 0.31 or less.

[0059] The thickness (d) and width (W) of the electrode body 3 at the axial center were measured, and the cross-sectional areas (SA, SB) were calculated from the following equations: d / 2 means the radius of the curved portion 21 .

[0060] SA=d×(Wd)

[0061] SB=((d / 2)×(d / 2))×π

[0062] In addition, the cross-sectional areas (SA, SB) can also be measured by image analysis of the cross section X.

[0063] The ratio (K / W) of the length (K) of the positive electrode mixed material layer 41 along the axial direction of the electrode body 3 to the length (W) in the width direction of the electrode body 3 is preferably greater than 1.6. Here, the length in the width direction refers to the length in the direction perpendicular to the axial direction and the thickness direction of the electrode body 3. Hereinafter, the ratio (K / W) is sometimes referred to as the aspect ratio. If the aspect ratio (K / W) is greater than 1.6, it is difficult for the electrolyte to be squeezed out from both ends of the length direction of the flat portion 20 (the axial ends of the electrode body 3) during charging. In addition, the electrolyte is easily squeezed out from both ends of the width direction of the flat portion 20 toward the direction of the curved portion 21, and the storage function of the non-aqueous electrolyte based on the curved portion 21 is easily reflected. The upper limit value of the aspect ratio (K / W) is not particularly limited, and is preferably less than 3.0.

[0064] [positive electrode]

[0065] As described above, the positive electrode 4 has a positive electrode core 40 and a positive electrode mixed material layer 41 formed on both sides of the positive electrode core 40. For the positive electrode core 40, a foil of a metal such as aluminum or aluminum alloy that is stable within the potential range of the positive electrode 4, a film obtained by configuring the metal on the surface, etc. can be used. The positive electrode mixed material layer 41 includes a positive electrode active material, a conductive material, and a binding material. The positive electrode 4 can be manufactured by applying a positive electrode mixed material slurry including a positive electrode active material, a conductive material, a binding material, and a dispersion medium to the positive electrode core 40, drying the coating and removing the dispersion medium, compressing the coating and forming the positive electrode mixed material layer 41 on both sides of the positive electrode core 40.

[0066] The positive electrode active material is composed of a lithium-containing transition metal composite oxide as a main component. As the metal elements contained in the lithium-containing transition metal composite oxide, Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, etc. can be listed. An example of a preferred lithium-containing transition metal composite oxide is a composite oxide including at least one of Ni, Co, and Mn. In addition, inorganic compound particles such as aluminum oxide and lanthanum-containing compounds can be adhered to the particle surface of the lithium-containing transition metal composite oxide.

[0067] As the conductive material included in the positive electrode mixed material layer 41, carbon materials such as carbon black, acetylene black, Ketjen black, and graphite can be exemplified. As the binding material included in the positive electrode mixed material layer 41, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. These resins and cellulose derivatives such as carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc. can be used simultaneously.

[0068] [negative electrode]

[0069] As described above, the negative electrode 5 has a negative electrode core 50 and a negative electrode mixed material layer 51 formed on both sides of the negative electrode core 50. For the negative electrode core 50, a foil of a metal such as copper or copper alloy that is stable within the potential range of the negative electrode 5, a film obtained by configuring the metal on the surface layer, etc. can be used. The thickness of the negative electrode core 50 is, for example, 5 μm or more and 20 μm or less. The negative electrode mixed material layer 51 includes a negative electrode active material and a binding material. The thickness of the negative electrode mixed material layer 51 is, for example, 50 μm or more and 150 μm or less on one side of the negative electrode core 50, preferably 80 μm or more and 120 μm or less. The negative electrode 5 can be manufactured by applying a negative electrode mixed material slurry including a negative electrode active material and a binding material to the negative electrode core 50, drying the coating and removing the dispersion medium, compressing the coating and forming the negative electrode mixed material layer 51 on both sides of the negative electrode core 50.

[0070] In the negative electrode mixed material layer 51, as the negative electrode active material, for example, a carbon-based active material that reversibly stores and releases lithium ions is included. Preferred carbon-based active materials are natural graphites such as flaky graphite, block graphite, and earthy graphite, block artificial graphite (MAG), and artificial graphites such as graphitized mesophase carbon microbeads (MCMB). In addition, for the negative electrode active material, a Si-based active material composed of at least one of Si and a Si-containing compound can be used, and a carbon-based active material and a Si-based active material can also be used at the same time.

[0071] As in the case of the positive electrode 4, for the binder included in the negative electrode mixed material layer 51, fluororesins such as PTFE and PVdF, PAN, polyimide, acrylic resin, polyolefin, etc. can be used, preferably styrene-butadiene rubber (SBR). In addition, CMC or its salt, polyacrylic acid (PAA) or its salt, PVA, etc. can be included in the negative electrode mixed material layer 51. CMC or its salt functions as a thickener for adjusting the negative electrode mixed material slurry to an appropriate viscosity range, and also functions as a binder like SBR.

[0072] A preferred example of the negative electrode mixed material layer 51 includes a negative electrode active material having a volume-based median diameter of 8 μm or more and 12 μm or less, SBR and CMC or a salt thereof. The volume-based median diameter is the particle size at which the volume cumulative value is 50% in the particle size distribution measured by the laser diffraction scattering method, also known as the 50% particle size (D50) or median diameter. The packing density of the negative electrode mixed material layer 51 is mainly determined by the packing density of the negative electrode active material, and the D50, particle size distribution, shape, etc. of the negative electrode active material have a great influence on the packing density. Relative to the mass of the negative electrode mixed material layer 51, the content of SBR, CMC or a salt thereof is preferably 0.1 mass % or more and 5 mass % or less, and more preferably 0.5 mass % or more and 3 mass % or less.

[0073] The negative electrode mixed material layer 51 includes a first region 51A located in the flat portion 20 of the electrode body 3 and a second region 51B located in a pair of curved portions 21, and the ratio (B / A) of the packing density (B) of the second region 51B to the packing density (A) of the first region 51A is greater than 0.75 and less than 0.95. In other words, the packing density of the negative electrode mixed material layer 51 in the curved portion 21 of the electrode body 3 is greater than 0.75 times and less than 0.95 times the packing density in the flat portion 20. When the packing density ratio (B / A) deviates from this range, as shown in the embodiments / comparative examples described later, good cycle characteristics cannot be ensured. The packing density ratio (B / A) is more preferably greater than 0.78 and less than 0.93, and particularly preferably greater than 0.80 and less than 0.92.

[0074] The porosity of the first region 51A is preferably 38% to 48%, more preferably 40% to 46%. The porosity of the second region 51B is preferably 48% to 59%, more preferably 50% to 57%. Within this range, the cycle characteristics are more effectively improved.

[0075] The second region 51B (curved portion 21) with a low packing density is superior to the first region 51A (flat portion 20) with a high packing density in terms of retention of the non-aqueous electrolyte in the negative electrode mixed material layer 51. When the packing density ratio (B / A) is 0.75 or more and 0.95 or less, the non-aqueous electrolyte squeezed out of the flat portion 20 can be efficiently stored in the curved portion 21, and when the volume of the flat portion 20 shrinks, the electrolyte stored in the curved portion 21 is quickly returned to the flat portion 20. As a result, it is possible to suppress the shortage of electrolyte in the flat portion 20 and the resulting reduction in cycle characteristics.

[0076] The packing density (A, B) of the first region 51A and the second region 51B is not particularly limited as long as it satisfies the above packing density ratio (B / A), but is preferably 0.9 g / cm 3 More preferably, 1.0 g / cm 3 The packing density (A) of the first region 51A is, for example, 1.15 g / cm 3 Above and 1.35g / cm 3 Below, or 1.20g / cm 3 Above and 1.30g / cm 3 The packing density (B) of the second region 51B is, for example, 0.95 g / cm 3 Above and 1.15g / cm 3 Below, or 1.00g / cm 3 Above and 1.10g / cm 3 the following.

[0077] The packing density (A) of the first region 51A is preferably substantially uniform throughout the first region 51A. Similarly, the packing density (B) of the second region 51B is preferably substantially uniform throughout the second region 51B. However, in a portion of the first region 51A, there may be a portion with a lower packing density than other portions or a portion with a higher packing density than other portions (the same applies to the second region 51B). The mass of the negative electrode mixed material layer 51 per unit area of ​​the negative electrode core 50 and the thickness of the negative electrode mixed material layer 51 are measured, and the mass is divided by the thickness to obtain the packing density (A, B).

[0078] The packing density ratio (B / A) can be controlled within a range of greater than 0.75 and less than 0.95 by adjusting the extrusion conditions when the wound body of the positive electrode 4, the negative electrode 5, and the separator 30 is formed into a flat shape. Specifically, the packing density ratio (B / A) can be controlled by appropriately changing the extrusion temperature, the extrusion pressure, and the extrusion time. The packing density ratio (B / A) can also be controlled by changing the amount of negative electrode mixed material slurry applied at the portion that becomes the first region 51A of the negative electrode core 50 and the portion that becomes the second region 51B. However, from the perspective of productivity, it is preferred to control the packing density ratio (B / A) by changing the extrusion conditions after forming the negative electrode mixed material layer 51 with a substantially uniform packing density. The above-mentioned cross-sectional area ratio (SB / SA) can also be controlled by the extrusion conditions.

[0079] An example of an extrusion temperature is 60°C or more and 90°C or more than 70°C or less than 80°C. An example of an extrusion time is 5 minutes or more, or 15 minutes or more, or 30 minutes or more. The upper limit of the extrusion time is not particularly limited, but is preferably 60 minutes or less from the perspective of productivity. Under the same conditions of extrusion temperature and time, the higher the extrusion pressure, the higher the packing density (A) of the first region 51A, and the easier it is for the packing density ratio (B / A) to become smaller. On the other hand, the lower the extrusion pressure, the lower the packing density (A) of the first region 51A, and the easier it is for the packing density ratio (B / A) to become larger. An example of an extrusion pressure is 90kN or more and 115kN or less. In addition, the higher the extrusion pressure, the smaller the cross-sectional area ratio (SB / SA), and the lower the extrusion pressure, the easier it is for the cross-sectional area ratio (SB / SA) to become larger.

[0080] [Partition]

[0081] A porous sheet having ion permeability and insulation is used for the separator 30. The separator 30 (porous sheet) includes, for example, a porous substrate having at least one selected from polyolefin, polyvinylidene fluoride, polytetrafluoroethylene, polyimide, polyamide, polyamideimide, polyethersulfone, polyetherimide, and aromatic polyamide as a main component. Among them, polyolefin is preferred, and polyethylene and polypropylene are particularly preferred.

[0082] The separator 30 may be composed only of a porous substrate made of resin, or may be a multilayer structure in which a heat-resistant layer including inorganic particles is formed on at least one surface of the porous substrate. In addition, the porous substrate made of resin may have a multilayer structure such as polypropylene / polyethylene / polypropylene. The thickness of the separator 30 is, for example, greater than 10 μm and less than 30 μm. For example, the average pore size of the separator 30 is greater than 0.02 μm and less than 5 μm, and the porosity is greater than 30% and less than 70%. Generally, the electrode body 3 includes two separators 30, and the same material can be used for each separator 30.

[0083] The separator 30 includes a first region located at the flat portion 20 of the electrode body 3 and a second region located at a pair of curved portions 21, and the ratio (D / C) of the air permeability (D) of the second region to the air permeability (C) of the first region can be 0.5 or more and 0.9 or less. In other words, the air permeability of the separator 30 in the curved portion 21 of the electrode body 3 can be 0.5 times or more and 0.9 times or less of the air permeability in the flat portion 20. If the air permeability ratio (D / C) is within this range, the retention of the non-aqueous electrolyte in the curved portion 21 is further improved, and further improvement in the cycle characteristics can be achieved. The air permeability ratio (D / C) is more preferably 0.52 or more and 0.86 or less, and particularly preferably 0.6 or more and 0.8 or less. The air permeability (s / 100cc) of the separator 30 can be measured using an air permeability measuring device (Kumagai Riki Industry Wangjian Smoothness / Air Permeability Tester: Product No. 2040-C).

[0084] The air permeability (C) of the first region of the separator 30 is not particularly limited as long as it satisfies the air permeability ratio (D / C), and is preferably 250 s / 100 cc or more and 450 s / 100 cc or less. The air permeability (D) of the second region of the separator 30 is the same as long as it satisfies the air permeability ratio (D / C), and is not particularly limited, and is preferably 150 s / 100 cc or more and 250 s / 100 cc or less. If the air permeability (C, D) is within this range, the output characteristics and insulation properties can be well maintained, and the cycle characteristics can be improved.

[0085] [Example]

[0086] Hereinafter, the present invention will be further described by way of examples, but the present invention is not limited to these examples.

[0087] <Example 1>

[0088] [Production of positive electrode]

[0089] As the positive electrode active material, LiNi 0.35 Co 0.35 Mn 0.30A lithium-containing transition metal composite oxide represented by O2. A positive electrode active material, acetylene black and polyvinylidene fluoride (PVdF) are mixed in a solid content mass ratio of 97:2:1 to prepare a positive electrode mixed material slurry using N-methyl-2-pyrrolidone (NMP) as a dispersion medium. Next, the positive electrode mixed material slurry is applied on both sides of a positive electrode core body composed of a strip of aluminum foil with a width of 127 mm (coating width 110 mm = length (K) of the positive electrode mixed material layer along the axial direction of the electrode body), and after the coating is dried, the coating is compressed to form a positive electrode mixed material layer on both sides of the core body. The core body is cut into a given electrode size to produce a positive electrode.

[0090] [Production of negative electrode]

[0091] Graphite was used as the negative electrode active material. The negative electrode active material, sodium salt of CMC and dispersion of SBR were mixed at a solid content mass ratio of 98.7:0.7:0.6 to prepare a negative electrode mixed material slurry using water as the dispersion medium. Next, the negative electrode mixed material slurry was applied to both sides of a negative electrode core body composed of a strip of copper foil with a width of 130 mm (coating width 115 mm). After the coating film was dried, the coating film was compressed and a filling density of 1.07 g / cm was formed on both sides of the core body. 3 The core is cut into a given electrode size to produce a negative electrode.

[0092] [Production of electrode body]

[0093] After the positive electrode and the negative electrode are wound through a strip-shaped separator with a width of 120 mm, the wound body is extruded in the radial direction and formed into a flat shape to produce a wound electrode body. The structure obtained by stacking the separator / positive electrode / separator / negative electrode in the order is wound on a cylindrical winding core to form a wound body (the same material is used for the two separators). In addition, the positive electrode and the negative electrode are wound so that the exposed parts of the respective core bodies are located on the axial opposite sides of the wound body. The extrusion conditions of the wound body are set to an extrusion temperature of 75°C, an extrusion pressure of 100 kN, and an extrusion time of 30 minutes. Three electrode bodies were made in the same way, and when the thickness was measured in the axial direction and the center of the width direction of the electrode body, the average thickness (d) was 15.7 mm. The axial length of the electrode body is 144 mm, the width (W) is 57.1 mm, and the aspect ratio (K / W) is 1.93.

[0094] [Preparation of non-aqueous electrolyte]

[0095] LiPF6 was added to a mixed solvent obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a volume ratio of 3:3:4 (25°C, 1 atmosphere) to a concentration of 1 mol / L, and vinylene carbonate was further added to a concentration of 0.3% by mass to prepare a non-aqueous electrolyte.

[0096] [Fabrication of non-aqueous electrolyte secondary battery]

[0097] The electrode body, the non-aqueous electrolyte and the square battery shell are used to make a non-aqueous electrolyte secondary battery (square battery). The positive terminal is mounted on the sealing plate constituting the battery shell, and the positive electrode collector is connected to the positive terminal. In addition, the negative terminal is mounted on the sealing plate, and the negative electrode collector is connected to the negative terminal. Moreover, the positive electrode collector is welded to the exposed part of the core of the positive electrode, and the negative electrode collector is welded to the exposed part of the core of the negative electrode. In the state where the electrode body integrated with the sealing plate is arranged in an insulating sheet formed into a box shape, it is contained in a square bottomed cylindrical outer box (lateral length 148.0mm (internal dimension 146.8mm), thickness 17.5mm (internal dimension 16.5mm), height 65.0mm (internal dimension 64.0mm)) constituting the battery shell, and the opening of the outer box is blocked with a sealing plate. After injecting 65 g of electrolyte from the electrolyte injection hole of the sealing plate to fully impregnate the electrode body with the nonaqueous electrolyte, temporary charging was performed and the sealing plug was installed in the injection hole to obtain a nonaqueous electrolyte secondary battery (battery capacity: 8 Ah).

[0098] <Example 2>

[0099] In the production of the electrode body, in addition to the use of the winding body before extrusion, the filling density of the negative electrode mixed material layer is 1.01g / cm 3 The electrode body and the nonaqueous electrolyte secondary battery were produced in the same manner as in Example 1 except that the negative electrode was changed to 115 kN and the pressing pressure of the winding body was changed to 115 kN. The thickness of the electrode body was 15.2 mm and the width (W) was 57.5 mm.

[0100] <Example 3>

[0101] In the production of the electrode body, in addition to the use of the winding body before extrusion, the filling density of the negative electrode mixed material layer is 1.11g / cm 3 The electrode body and the nonaqueous electrolyte secondary battery were produced in the same manner as in Example 1 except that the extrusion pressure of the winding body was changed to 90 kN. The thickness of the electrode body was 16.4 mm and the width (W) was 56.9 mm.

[0102] <Comparative Example 1>

[0103] In the production of the electrode body, in addition to the use of the winding body before extrusion, the filling density of the negative electrode mixed material layer is 1.01g / cm 3 The electrode body and the nonaqueous electrolyte secondary battery were produced in the same manner as in Example 1 except that the pressing pressure of the winding body was changed to 110 kN. The thickness of the electrode body was 15.8 mm and the width (W) was 57.5 mm.

[0104] <Comparative Example 2>

[0105] The electrode body and the nonaqueous electrolyte secondary battery were produced in the same manner as in Example 1 except that the pressing pressure of the wound body was changed to 122 kN. The electrode body had a thickness of 14.8 mm and a width (W) of 57.1 mm.

[0106] <Comparative Example 3>

[0107] The electrode body and the nonaqueous electrolyte secondary battery were produced in the same manner as in Comparative Example 1, except that the pressing pressure of the wound body was changed to 89 kN. The electrode body had a thickness of 16.7 mm and a width (W) of 57.1 mm.

[0108] <Comparative Example 4>

[0109] In the production of the electrode body, in addition to the use of the winding body before extrusion, the filling density of the negative electrode mixed material layer is 1.13g / cm 3 The electrode body and the nonaqueous electrolyte secondary battery were produced in the same manner as in Example 1 except that the pressing pressure of the winding body was changed to 106 kN. The thickness of the electrode body was 15.7 mm and the width (W) was 56.7 mm.

[0110] <Comparative Example 5>

[0111] The electrode body and the nonaqueous electrolyte secondary battery were produced in the same manner as in Comparative Example 1, except that the pressing pressure of the wound body was changed to 122 kN. The electrode body had a thickness of 14.8 mm and a width (W) of 57.5 mm.

[0112] [Packing density of negative electrode mixture layer (A, B)]

[0113] Each battery of the embodiment and the comparative example was disassembled, and the thickness of the negative electrode in the flat part and the curved part of the electrode body was measured with a micrometer. At this time, the thickness of the negative electrode in the flat part was measured at the position of the second layer from the outermost periphery of the negative electrode closest to the outer peripheral surface of the electrode body in the center of the length direction and the width direction of the flat part. As in the case of the flat part, the thickness of the negative electrode in the curved part was measured at the position of the second layer from the outermost periphery of the negative electrode to the inner side. The packing density of the negative electrode mixed material layer in the flat part and the packing density of the negative electrode mixed material layer in the curved part (A, B) were calculated by the following mathematical formula. The calculated packing density (A, B) and packing density ratio (B / A) are shown in Table 1.

[0114] (Packing density) = (mass of negative electrode mixture layer per unit area) ÷ (negative electrode thickness - core thickness)

[0115] [Cross-sectional area SA, SB]

[0116] For each of the disassembled batteries of the examples and comparative examples, the following mathematical formula was used to calculate the cross-sectional area ratio (SB / SA) from the thickness (d) and width (W) of the electrode body. Table 1 shows the calculated cross-sectional area ratio (SB / SA).

[0117] SA=d×(Wd)

[0118] SB=((d / 2)×(d / 2))×π

[0119] [Evaluation of capacity maintenance rate]

[0120] Each battery of the embodiment and the comparative example was charged at a constant current of 8.0 A at 25°C until the battery voltage became 4.1 V, and then discharged at a constant current of 8.0 A until the battery voltage became 2.5 V. This charge and discharge cycle was repeated 100 times, and the ratio of the discharge capacity of the 100th cycle to the discharge capacity of the 1st cycle (capacity maintenance rate) was calculated. The capacity maintenance rate of each battery is shown in Table 1 as a relative value with the capacity maintenance rate of the battery of Example 1 being 100.

[0121] [Output evaluation]

[0122] The battery after 100 cycles was charged at 25°C until the depth of charge (SOC) of the battery became 50%. Next, at 25°C, discharge was performed for 10 seconds at current values ​​of 60A, 120A, 180A, and 240A, respectively, and the battery voltage was measured. Moreover, the current value at 3.0V was calculated based on the linear line obtained by plotting each current value and battery voltage, and the output value was calculated. In addition, by charging at a constant current of 8.0A, the depth of charge shifted due to discharge was returned to the original depth of charge. The output of each battery is shown in Table 1 as a relative value with the output of the battery of Example 1 being set to 100.

[0123] [Evaluation of lithium precipitation]

[0124] Each battery after the cycle test was disassembled, the negative electrode surface was visually checked, and the presence or absence of Li precipitation was evaluated. The evaluation results are shown in Table 1, where no Li precipitation was observed over the entire length of the negative electrode, and where Li precipitation was observed.

[0125] [Table 1]

[0126]

[0127] It can be understood from the evaluation results shown in Table 1 that the cycle characteristics of the batteries of the embodiments are better than those of the batteries of the comparative examples. The capacity retention rate and output after the above-mentioned cycle test of the batteries of the embodiments are high. In addition, in the batteries of the embodiments, the precipitation of Li was not confirmed on the negative electrode surface. On the other hand, the capacity retention rate and / or output after the cycle test of the batteries of the comparative examples were low, and in addition, except for the battery of comparative example 3, the precipitation of Li was confirmed on the negative electrode surface.

[0128] In the battery of Comparative Example 1, the cross-sectional area ratio (SB / SA) is equivalent to that of the battery of Example 1, but the packing density ratio (B / A) of the negative electrode mixed material layer in the flat portion A and the curved portion B is as small as 0.70. That is, it can be seen that the packing density of the negative electrode mixed material layer in the flat portion becomes relatively large, and the extrusion and return of the electrolyte to the curved portion are reduced relative to the volume change of the electrode body accompanying charging and discharging. As a result, it is believed that the electrolyte in the flat portion is insufficient or dried up, the capacity retention rate and output are reduced, and Li is precipitated on the negative electrode surface. In addition, in the comparative examples other than Comparative Example 3, Li precipitation is confirmed on the flat portion throughout the entire length of the negative electrode. In particular, precipitation is significant in the central portion of the axial and width directions of the electrode body where the volume change is large.

[0129] In the battery of Comparative Example 2, the packing density ratio (B / A) is equivalent to that of the battery of Example 1, but the cross-sectional area ratio (SB / SA) is as small as 0.275. In this case, it is believed that since the amount of electrolyte that can be stored in the curved portion is reduced, the electrolyte is insufficient or dried up in the flat portion, and in the cycle test, the capacity retention rate and output are reduced, and Li is precipitated on the negative electrode surface.

[0130] In the battery of Comparative Example 3, the packing density ratio (B / A) is equivalent to that of the battery of Example 1, but the cross-sectional area ratio (SB / SA) is as large as 0.325. In this case, since the electrolyte is fully stored in the curved portion, the capacity retention rate after the cycle test is good, and no Li precipitation is confirmed on the negative electrode surface. On the other hand, since the inter-electrode distance between the positive and negative electrodes in the curved portion is longer than that in the flat portion, there is a tendency for the resistance to increase according to the relationship between the ion conductivity in the electrolyte. In the battery of Comparative Example 3, it can be considered that the output is reduced due to the large curved portion.

[0131] In the battery of Comparative Example 4, the cross-sectional area ratio (SB / SA) is equivalent to that of the battery of Example 1, but the packing density ratio (B / A) is as large as 0.98. That is, since the packing density of the flat portion is relatively small, the amount of electrolyte extruded in the winding axial direction and perpendicular direction of the electrode body is large relative to the expansion and contraction of the electrode body caused by charging and discharging. In this case, it can be considered that the storage function of the electrolyte in the curved portion is not fully reflected, the electrolyte is insufficient or dried up in the flat portion, and in the cycle test, the capacity retention rate and output are reduced, and Li is precipitated on the negative electrode surface.

[0132] In the battery of Comparative Example 5, it is also considered that the electrolyte in the flat portion was insufficient or dried up, the capacity retention rate and the output were reduced, and Li was deposited on the negative electrode surface.

[0133] <Example 4>

[0134] In the preparation of the electrode body, except that the coating width of the positive electrode mixed material slurry was set to 92.0 mm, the coating width of the negative electrode mixed material slurry was set to 94.1 mm, and the aspect ratio (K / W) was changed to 1.61, the electrode body and the non-aqueous electrolyte secondary battery (battery capacity: 6.5 Ah) were prepared in the same manner as in Example 1. No Li precipitation was confirmed on the negative electrode surface.

[0135] <Example 5>

[0136] In the preparation of the electrode body, except that the coating width of the positive electrode mixed material slurry was set to 85.0 mm, the coating width of the negative electrode mixed material slurry was set to 83.6 mm, and the aspect ratio (K / W) was changed to 1.49, the electrode body and the non-aqueous electrolyte secondary battery (battery capacity: 5.8 Ah) were prepared in the same manner as in Example 1. No Li precipitation was confirmed on the negative electrode surface.

[0137] [Table 2]

[0138]

[0139] As shown in Table 2, in the battery of Example 5, the packing density ratio (B / A) and the cross-sectional area ratio (SB / SA) are equivalent to those of the batteries of Examples 1 and 4, and the aspect ratio (K / W) is smaller than that of the batteries of Examples 1 and 4. That is, it can be considered that the axial length of the flat portion is relatively short, and when the electrode body expands with charging, the electrolyte exceeds the formation range of the positive electrode mixed material layer and is easily squeezed out to both sides of the axial direction of the electrode body. Therefore, it can be considered that the electrolyte squeezed out of the electrode body is difficult to return to the center of the electrode body, and the cycle characteristics are slightly reduced.

Claims

1. A non-aqueous electrolyte secondary battery, comprising: a flat wound electrode body, the electrode body being formed by winding a positive electrode including a positive electrode mixed material layer and a negative electrode including a negative electrode mixed material layer with a separator interposed therebetween, and having a flat portion and a pair of curved portions; a non-aqueous electrolyte; and a battery case accommodating the electrode body and the non-aqueous electrolyte, characterized in that: The negative electrode mixed material layer includes a first region located in the flat portion of the electrode body and a second region located in the pair of curved portions, wherein a ratio B / A of a packing density B of the second region to a packing density A of the first region is greater than or equal to 0.75 and less than or equal to 0.95, In a cross section perpendicular to the axial direction and passing through the axial center of the electrode body, a ratio SB / SA of a cross-sectional area SB of the pair of curved portions to a cross-sectional area SA of the flat portion is 0.28 or more and 0.32 or less, A ratio K / W of a length K of the positive electrode mixture layer along the axial direction to a length W in a direction perpendicular to the axial direction and the thickness direction of the electrode body is 1.61 or more and 1.93 or less.

2. The nonaqueous electrolyte secondary battery according to claim 1, characterized in that: The ratio B / A is 0.78 or more and 0.93 or less.

3. The nonaqueous electrolyte secondary battery according to claim 1, characterized in that The porosity of the first region is 38% or more and 48% or less. The porosity of the second region is 48% or more and 59% or less.

4. The nonaqueous electrolyte secondary battery according to claim 1, characterized in that: The negative electrode mixed material layer includes: a negative electrode active material having a volume-based median diameter of 8 μm or more and 12 μm or less, styrene-butadiene rubber, and carboxymethyl cellulose or a salt thereof.

5. The non-aqueous electrolyte secondary battery according to claim 1, characterized in that: The nonaqueous electrolyte solution is accommodated in an amount of 55 g to 75 g both inclusive in the battery case.